Evaluation of the EasyScreen™ ESBL/CPO Detection Kit for the Detection of ß-Lactam Resistance Genes - Camille Gonzalez; Saoussen Oueslati; Laura Biez; Laurent Dortet; Thierry Naas (Diagnostics, 2022)
Early detection of multidrug resistant bacteria is of paramount importance for implementing appropriate infection control strategies and proper antibacterial therapies. We have evaluated a novel real-time PCR assay using fluorescent probes and 3base® technology, the EasyScreenTM ESBL/CPO Detection Kit (Genetic Signatures, Newtown, Australia), for the detection of 15 β-lactamase genes (blaVIM, blaNDM, blaIMP, blaOXA-48, blaKPC, blaOXA-23, blaOXA-51, blaSME,blaIMI, blaGES,blaTEM,blaSHV, blaCTX-M,blaCMY, blaDHA) and colistin resistance mcr-1 gene from 341 bacterial isolates (219 Enterobacterales, 66 P. aeruginosa and 56 A. baumannii) that were grown on Mueller–Hinton (MH) agar plates. One colony was suspended in provided extraction buffer, which lyses and converts the nucleic acids into a 3base®-DNA form (cytosines are converted into uracil, and subsequently thymine during PCR). The converted bacterial DNA is then added to the 6 PCR mixes, with primers for three targets plus one internal control. The EasyScreenTM ESBL/CPO Detection Kit was able to detect the 5-major (NDM, VIM, IMP, KPC, OXA-48) and 2-minor (IMI, Sme) carbapenemases and their variants irrespective of the species expressing them with nearly 100% sensitivity and specificity. With cephalosporinases CMY (82% of sensitivity) and DHA (87% of sensitivity) detection of chromosomally encoded variants was less efficient. Similarly, the chromosomally encoded OXA-51 variants were not consistently detected in A. baumannii. Despite being capable of efficiently detecting blaCTX-M-, blaTEM-, blaSHV- and blaGES-like genes, the EasyScreen™ ESBL/CPO Detection Kit was not able to distinguish between penicillinases and ESBL-variants of TEM and SHV and between GES-ESBLs and GES-carbapenemases. As GES enzymes are still rare, their detection as an ESBL or a carbapenemase remains important. Detection of mcr-1 was efficient, but none of the other mcr-alleles were detected in the 341 bacterial isolates tested. The EasyScreenTM ESBL/CPO Detection Kit is adapted for the detection of the most prevalent carbapenemases encountered in Gram-negatives isolated worldwide.